Komparasi Karakteristik Papan Sawit dengan Papan Furnitur Berbahan Kayu Plajau - Yudi Dwianda (Jurnal Rekayasa Proses dan Industri Terapan, 2024)
In general, furniture is made from hard and durable wood. But now hard and durable wood is starting to be difficult to find. So, alternative materials are sought that are easy to get and cheap. ASTM D638 standard wood for Tensile testing, the strength results of palm wood aged 16-20 years are 4.47 MPa, 14.41 MPa for 21-25 year old palm wood while Plajau wood’s strength is 114.77 MPa. Standard SNI 03-3958-1995 for compression testing showed that the strength of palm wood aged 16-20 years was 9.93 MPa, palm wood aged 21-25 years was 10.05 MPa and plajau wood was 55.27 MPa Standard SNI 03- 3959-1995 for the Bending test, the results showed that the strength of palm wood aged 16-20 years was 4.50 N/mm2, palm wood aged 21-25 years was 21.17 N/mm2 and plajau wood was 91.66 N/mm2. Based on the results of the study it can be explained that oil palm wood aged 16-20 years and 21-25 years cannot be used as raw material for making furniture.